Repeat pregnancy during adolescence and educational level in Brazil. - Domenico, Juliana; Guimarães, Patricia; Guillen, Luis Carlos; Camargo, Kenneth; Sobrino, Rejane; Coeli, Claudia (International Journal of Population Data Science, 2018)
Introduction Repeat pregnancy among adolescents is associated with preexisting disadvantages related to the adolescent’s social and cultural background. In Brazil, there is a lack of studies that evaluate repeat pregnancy during the entire adolescence period. Record linkage is a useful tool for following adolescents after the birth of their first child. Objectives and Approach To estimate pregnancy repetition during adolescence and to evaluate the effect of inadequate schooling during the first pregnancy on repetition in a cohort of adolescents in Rio de Janeiro City who had their first live-born child between the ages of 15 and 18. We carried out a non-concurrent cohort study using probabilistic record linkage techniques. The association between mother’s schooling and at least one repeat pregnancy during adolescence was evaluated through risk ratios adjusted for mother’s age, estimated using generalized linear models with binomial distribution and Neperian logarithm function. We also evaluated the interdelivery interval. Results 9,285 adolescents were included in the study. Of these, 29.4% had inadequate schooling at the time their first child was born and 9.9% had at least on repeat pregnancy during adolescence. The risk of repeat pregnancy was significantly higher in the group with inadequate schooling (adjusted RR=1.19; 95% CI= 1.05-1.34), when compared with the group with adequate schooling. Half of the teenage mothers had an interval between the first and the second pregnancy of less than 24 months, with data showing no statistically significant difference between the two groups with respect to adequacy of mother’s schooling. Adolescents with more than one repeat pregnancy had the worst prenatal and labor care indicators, as well as the highest incidence of premature births. Conclusion/Implications Inadequate schooling at the time of the first child’s birth increases the risk of repeat pregnancies during adolescence. Additionally, inadequate schooling and a history of repeat pregnancies during adolescence are markers of populations that accumulate disadvantages in access to care and in pregnancy outcomes.